Yatiribeitani tsamiri: “el paujil cuando era una persona” - Cabello Chiricente, Caleb (2010)
In the ashaninka world view, it is considered that at the beginning the earth was inhabited by ashaninkas that became animals afterwards. This is a story that was originally told by the elders. The paujil (bird) was a person before, it lived in the top of a mountain with its relatives in a house. One day an ashaninka found the place were the paujil used to drink, from then on the contact with the paujil-man was established. When the paujil and the ashaninka hunter talked, the hunter asked the paujil not to cause more harm to the ashaninkas. Before saying good bye, the ashaninka received a pituca (tuber) as a gift, and this pituca turned into a paujil when the ashaninka arrived home.